A new type of aerodynamic measurement technology for vehicle model running on bridge under crosswind in wind tunnel test. Issue 13 (October 2022) - Zou, Yunfeng; Liu, Zhipeng; Shi, Kang; He, Xuhui; Deng, Honggui
The existing moving vehicle models generally require a long test-track to realize the acceleration and deceleration processes and the negative effect of data cables is inevitably for the wind pressure measurement using the traditional pressure scanning system. To address the technical obstacle for moving vehicle models in wind tunnel tests, a new type of aerodynamic measurement technology is presented in this study. Firstly, a piece of new kinetic equipment, a U-Shaped launching ramp, is proposed. The U-Shaped launching ramp can realize the acceleration and deceleration of the vehicle model by gravity and makes full use of the test section of the wind tunnel. Then, a wireless pressure acquisition system is developed to virtually eliminate the negative effects of the inertia and friction forces. By comparing with the conventional wind pressure test data, the proposed wireless pressure acquisition system presents a higher accuracy and fully satisfies the test requirement for the moving vehicle-bridge system. From the scaled test, it is confirmed that the aerodynamic forces of the moving vehicle model are larger than that of the static one, implying that the moving test is necessary for studying the aerodynamic characteristics of the vehicle-bridge coupling system.